2018
DOI: 10.2320/matertrans.m2018073
|View full text |Cite
|
Sign up to set email alerts
|

Joining of Metals by Super-Spread Wetting on Surface Fine Crevice Structure Created by Reduction-Sintering Copper Oxide Powder

Abstract: A surface fine crevice structure, created by laser irradiation, results in a region-selective super-spread wetting and the joining of metals is possible by taking advantage of this wetting. Through reduction-sintering of copper oxide (CuO) powder, we are able to obtain a sintered-Cu layer that possesses a complex sponge-like structure in which a porous network is formed. The wettability of molten tin (Sn) on the obtained sintered-Cu layer is investigated to confirm whether the super-spread wetting occurs on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Our research group [13][14][15] originally found that super-spread wetting occurs on the surface fine porous structure that is produced by atmospheric oxidation-reduction treatment of a metal surface. In further studies, we found two kinds of surface fine crevice structures that can promote region-selective super-spread wetting of liquid metals: namely, (1) a laser-irradiated surface fine crevice structure, created by laser irradiation [16][17][18][19][20] and (2) a powder-based surface fine crevice structure, created by reduction sintering of an oxide powder [21] on copper and iron surfaces. Super-spread wetting of these two surface fine crevice structures showed that similar and dissimilar metal-to-metal joining, such as Cu-Cu [16,17,21] and Cu-Fe [20] joining, can be achieved.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our research group [13][14][15] originally found that super-spread wetting occurs on the surface fine porous structure that is produced by atmospheric oxidation-reduction treatment of a metal surface. In further studies, we found two kinds of surface fine crevice structures that can promote region-selective super-spread wetting of liquid metals: namely, (1) a laser-irradiated surface fine crevice structure, created by laser irradiation [16][17][18][19][20] and (2) a powder-based surface fine crevice structure, created by reduction sintering of an oxide powder [21] on copper and iron surfaces. Super-spread wetting of these two surface fine crevice structures showed that similar and dissimilar metal-to-metal joining, such as Cu-Cu [16,17,21] and Cu-Fe [20] joining, can be achieved.…”
Section: Introductionmentioning
confidence: 96%
“…In further studies, we found two kinds of surface fine crevice structures that can promote region-selective super-spread wetting of liquid metals: namely, (1) a laser-irradiated surface fine crevice structure, created by laser irradiation [16][17][18][19][20] and (2) a powder-based surface fine crevice structure, created by reduction sintering of an oxide powder [21] on copper and iron surfaces. Super-spread wetting of these two surface fine crevice structures showed that similar and dissimilar metal-to-metal joining, such as Cu-Cu [16,17,21] and Cu-Fe [20] joining, can be achieved. Super-spread wetting is believed to be applicable to solving limitations of ceramic-to-metal joining caused by low wettability.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Gas-liquid, liquid-liquid, solidliquid in a porous medium or channel under supergravity condition can significantly improve the stress difference between two phases to strengthen the relative speed, reduce the role of liquid surface tension, and generate a great shearing force for stretching or tearing the liquid into micron or nanoscale liquid membrane and liquid droplets. [31][32][33] Compared with the conventional gravity field, the interphase area is greatly increased, the diffusivity of substances is obviously improved, the phase interface is fast updated, and the micromixing of different phases is accelerated, to greatly enhance the mass transfer of substance. Thus the supergravity technology has been studied in the following metallurgy fields: (a) removal of impurity elements (such as Fe, Si, and Cu) from molten metals, 27,34) (b) enrichment of valuable elements (such as Ti, V, RE, and P) from metallurgical slags, 25,28,30,31,[35][36][37][38][39][40][41] (c) separation of non-metallic inclusions (such as Al 2 O 3 particle) from molten metal, [42][43][44] and (d) refinement of the solidification structure of metal alloy (such as Al-Cu alloy).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have fabricated two types of surface fine crevice structures that can facilitate region-selective super-spread wetting by laser irradiation 47) and reduction-sintering of oxide powder on the metal surface. 8) These two types of surface fine crevice structures that display super-spread wetting may be suitable for micro joining to allow miniaturization of electronic components, such as joining microelectronic wires onto printed circuit boards. With regard to targeted joining over larger areas, it is considered that the methods used to fabricate surface fine crevice structure, i.e., laser irradiation and reduction-sintering of oxide powder, are unsuitable because they require the surface treatment of materials to be joined, which increases the process time and cost with joint area.…”
Section: Introductionmentioning
confidence: 99%